'All at Sea': Virginia Woolf, Walter Benjamin, and the Unknown German. Issue 2 (August 2021) - Schad, John
Abstract : On July 10, 1940, amidst fear of Nazi invasion, a prison ship, of sorts, left Liverpool, England, crammed full of over two thousand male 'Enemy Aliens' – Germans, Austrians, and some Italians. They were herded together, below deck, with all hatches sealed. Some were prisoners of war, some were passionate Nazis, but most were Jewish refugees. Among them was Walter Benjamin's estranged son, a young man of 22 years, Stefan Rafael Schoenflies Benjamin. Soon after boarding, however, the authorities mistakenly recorded his surname as Benjamini. 'All at Sea', John Schad's critical-creative piece, recounts events around 'the unknown German' on the vessel, playing richly on, and with, recognition effects around what is (un)familiarly known about Virginia Woolf, Walter Benjamin, and various kinds of connection between them and other figures from the period.